(untitled) (Research, Society and Development, 2021)
The objective of this study is to verify the knowledge of nursing care for tracheostomized patients hospitalized in a Medium-sized Hospital of the Taquari Valley-RS-Brazil. It is a descriptive, qualitative methodology. Data collection took place through interviews with guiding questions to nurses at the Medium-sized Hospital of Vale do Taquari. The study included 10 nurses who provide assistance and who accepted to answer the interview. The exclusion criterion was for nurses who were away from their activities. All study participants signed the Free and Informed Consent Form (ICF). The responses were analyzed and collected according to the content of Bardin (2011), and organized into four categories. From the results obtained, the proper assistance of the nurse to the tracheostomized patient is correctly observed. Through assistance to tracheostomized patients admitted to the Medium-sized Hospital of Vale do Taquari-RS-Brazil, it is concluded that the participants know the correct care and their respective care.